2010
DOI: 10.1029/2009jd012364
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor measurements at ALOMAR over a solar cycle compared with model calculations by LIMA

Abstract: [1] Microwave water vapor measurements between 40 and 80 km altitude over a solar cycle (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) were carried out in high latitudes at Arctic Lidar Observatory for Middle Atmosphere Research (ALOMAR) (69.29°N, 16.03°E), Norway. Some smaller gaps and three interruptions of monitoring in the winters 1996/1997 and 2005/2006 and from spring 2001 to spring 2002 occurred during this period. The observations show a distinct year-to-year variability not direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…The ionization and ion-chemistry calculations require appropriate minorconstituent models for NO and H 2 O, respectively. For H 2 O we have made an analytical approximation to the climatologies reported by Hartogh et al (2010) (from a decade of year-round measurements from Andenes, northern Norway) and by Rong et al (2010) (polar summer mesosphere in both hemispheres observed by the SOFIE instrument on the AIM satellite). This is illustrated in the right-hand panel of Fig.…”
Section: Ion and No Production Rate Modelmentioning
confidence: 99%
“…The ionization and ion-chemistry calculations require appropriate minorconstituent models for NO and H 2 O, respectively. For H 2 O we have made an analytical approximation to the climatologies reported by Hartogh et al (2010) (from a decade of year-round measurements from Andenes, northern Norway) and by Rong et al (2010) (polar summer mesosphere in both hemispheres observed by the SOFIE instrument on the AIM satellite). This is illustrated in the right-hand panel of Fig.…”
Section: Ion and No Production Rate Modelmentioning
confidence: 99%
“…Pronounced daily water variability is connected to planetary wave activity throughout the year (Hartogh et al, 2010). The largest water vapour concentrations have been found during summer because of intensified gravity wave upward propagation.…”
Section: Reactionmentioning
confidence: 99%
“…Recent research has been quite successful in mapping the water vapour pattern in the lower mesosphere and explaining possible mechanisms for cluster ion formation (Solomon et al, 1981;Gumbel and Witt, 2002;Sonnemann et al, 2005Sonnemann et al, , 2012Hervig and Siskind, 2006;Lossow et al, 2007;Grygalashvyly et al, 2009;Hartogh et al, 2010;Gabriel et al, 2011). However, the ionospheric parameter responses to water vapour variability in the mesosphere and the lower thermosphere are very complicated.…”
mentioning
confidence: 99%
“…On the other hand, the ground based instrument needs information about global scale waves from satellites to be able to draw conclusions about the observed variations. Ground based microwave spectroscopy is a well-established technique which has proven to be useful for observations of the water vapour mixing ratio (WVMR) on different time scales, from long term trends and seasonal behaviour to isolated events such as sudden stratospheric warmings (Hartogh and Jarchow, 1995;Nedoluha et al, 1996;Seele and Hartogh, 2000;Hartogh et al, 2010). The chemical lifetime of water vapour in the middle atmosphere is on the order of days to weeks (depending on altitude) which is similar to the characteristic dynamical time scale of interest and can therefore be used as a tracer molecule (Brasseur and Solomon, 1998).…”
Section: Introductionmentioning
confidence: 99%